Becoming Turkish : nationalist reforms and cultural negotiations in early republican Turkey, 1923-1945 - Yılmaz, Hale (Modern intellectual and political history of the Middle East., 2013)
In this ... book, [the author] uses hitherto unavailable archival material and oral history accounts to analyze aspects of everyday culture in interwar Turkey that scholars know about but have not looked at closely. Her wide-ranging examination of the social impact of Kemalist reforms shows that while people's responses ranged from enthusiastic approbation to intense hostility, most Turks found ways to adapt to state policies that aimed at transforming society. -- Houchang Chehabi, Professor of International Relations and History, Boston University